Impacts of child gender on parents' dominance in parent-child conversations - Crinis, La-Mia Juan (Nanyang Technological University, 2024)
Prior research on child gender’s effect on parental conversational dominance has narrowly focused on interruptions, neglecting other characteristics of conversational dominance (i.e., number of words, mean length of turns, ratio of wh-questions). It is crucial to investigate how parents model gender-specific conversational patterns as a potential basis for how children develop conversational dominance.